Kepastian Hukum Bagi Narapidana Pedofil Yang Diancam Pidana Tambahan Kebiri Kimia - Waluja, Herlin Djaja (Jurnal Hukum Statuta, 2021)
This study aims to find out the ratio legis of chemical castration penalty for convicted paedophiles in the child protection act. this type of research is normative legal research. The research used a statutory approach and a concept approach. the data used in this study is secondary data sources. The data collection technique conducted for this research was literature studies. The research showed that the number of pedophilia cases are increasing and growing in Indonesia, thus requiring a new innovation in implementing penalty towards perpetrators who deviate from the provisions of criminal sanctions in the criminal code.This is because the existing sanctions have not been effective in providing a deterrent effect towards the perpetrators. The ratio legis for additional penalty of chemical castration is based on the threats to children welfare (children's rights from various aspects) due to the increasing number of victims of sexual violence against children (male and female) committed by pedophiles.